MOLECULAR MARKER TECHNIQUES AND THEIR UTILITY IN TREE BREEDING - M. G. MALLIKARJUNA,; P. DHANANJAYA,; SANGH CHANDRAMOHAN,; FARZANA JABEEN, (The Bioscan, 2012)
Genetic markers are the useful source for diversity analysis and breeding programmes of any species. These markers are exploited at phenotypic, biochemical and nucleic acid level. The discovery of DNA based marker system revolutionised the breeding programs in economically important species including trees, crops and animals. The tree breeding is one of the components of silviculture and the conventional approach suffers from various drawbacks. Hence the application of molecular marker technology at this point able to answer most of these problems. Presently these techniques are exploited in various tree breeding species for diversity analysis at intra and inter-species level, fingerprinting of clones and varieties and linkage map construction for genes governing various traits of interest. So in this paper we emphasised on the need and available DNA based markers and their potential use for various strata of tree breeding.